THE TRANSFORMATION OF FAMILY STRUCTURES AND ITS IMPACT ON SOCIAL VALUES AND BEHAVIORS - Austríaco-Teixeira, Phelipe; Digiácomo, Eduardo; de Almeida, Dayse Coelho; Machado, Osmar Malta (Editora Impacto Científico, 2025)
Contemporary family structures undergo profound transformations that redefine social values and behaviors, driven by processes of individualization, secularization, and redefinition of gender roles. This study analyzes transformations in family structures and their impacts on social values and behaviors, investigating mechanisms through which changes in domestic arrangements affect socialization processes and identity construction. The research is justified by the need to systematize knowledge about relationships between family transformations and changes in social values, providing support for inclusive public policies. The general objective consists of analyzing transformations in contemporary family structures and their impacts on social values and behaviors. Methodologically, a qualitative exploratory approach is adopted through systematic literature review in international scientific databases, with thematic content analysis of 61 selected articles. Results show that diversification of family arrangements, including single-parent, blended, and same-sex families, reflects processes of expanding individual autonomy and redefining gender roles. It is concluded that family transformations exert profound impacts on moral values and social behaviors, requiring public policies that recognize the diversity of domestic arrangements and promote the quality of family relationships, regardless of their structural configuration. DOI: https://doi.org/10.56238/edimpacto2025.083-004